Left atrial appendage flow velocity predicts recurrence of atrial fibrillation after catheter ablation: A systematic review and meta-analysis - Chen, Pengfei; Shi, Yujiao; Ju, Jianqing; Pan, Deng; Miao, Lina; Guo, Xiaolin; Chen, Zhuhong; Du, Jianpeng (Frontiers in Cardiovascular Medicine, 2022)
Purpose There is increasing evidence that left atrial appendage flow velocity (LAAFV) is linked to the recurrence of atrial fibrillation (AF) after catheter ablation (CA), suggesting the potential predictable significance of LAAFV in this setting. We performed a systematic review and meta-analysis to assess whether LAAFV is association with AF recurrence after CA. Methods Up to May 1, 2022, six databases (PubMed, EMBASE, Web of Science, Cochrane Library, Scopus, and CINAHL) were searched for literature reporting the association between LAAFV and AF recurrence after CA. All statistical analyses were carried out using STATA version 16 software. Heterogeneity was determined by the Cochrane’s Q test and I2 statistics. The Newcastle-Ottawa Scale (NOS) was used to assess the methodological quality of each included study, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method was adopted to evaluate the quality of evidence. Result Sixteen studies with 5,006 AF patients after CA (1,479 patients with AF recurrence, 3,527 without AF recurrence) were included in the meta-analysis. The meta-analysis of 15 studies (16 data sets) showed that patients with recurrence exhibited lower LAAFV values than those without recurrence [standardized mean difference (SMD): −0.65, 95% CI: −0.88 to −0.42, P < 0.01]. Moreover, we evaluated the association of LAAFV and the risk of AF recurrence after CA. Nine studies (11 data sets) defined LAAFV as continuous variables, and the pooled analysis suggested that for every 1 cm/s rise in LAAFV values, the risk of AF recurrence after CA decreased by 3% [Odds Ratio (OR): 0.97, 95% CI: 0.95 to 0.99, P < 0.01]. Seven studies defined LAAFV as categorical variables, and the pooled analysis showed that lower LAAFV were associated with an increased risk of AF recurrence after CA [OR: 2.28, 95% CI: 1.46 to 3.57, P < 0.01]. The subgroup analyses showed that the association between LAAFV and AF recurrence after CA was not significantly affected by the AF type and ablation procedure. The NOS indicated that included studies were moderate to high quality, while the GRADE assessment suggested a low certainty of the evidence. Conclusion Lower LAAFV may be associated with an increased risk of AF recurrence after CA. Further studies with well designed and randomized studies for LAAFV should be conducted. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022333627].